Niobium-Titanium-Based Photocatalysts: Its Potentials for Free Cyanide Oxidation in Residual Aqueous Effluent - Barbosa López, Aida Liliana; Castro, Isel M. (Frontiers in Chemistry, 2020)
Organic compounds are employed as additives to increase the dissolution speed of gold, in concentrations around 1g/L when using cyanidation, thereby forming a residual aqueous effluent with high amounts of free cyanides and organic compounds that generates metallic complexes difficult to degrade. To increase the photodegradation efficiency, promising niobium and titanium porous materials are proposed as photocatalysts, due to their role in simultaneous oxidation and reduction reactions. In the process of cyanide oxidation, NbO5 .3H2O was doped with titanium oxalate (IV) of -0.5%, 1%, and 1.5%; and HTiNbO5 were synthesized, from the mixture of NbO5 with TiO2 Degussa-P25, by coprecipitation, impregnation, and solid state. The determination of its elemental composition, morphological and textural properties were carried out by using various XRD techniques, Raman spectroscopy, SEM / EDS and acidity by pyridine. The experiments of photocatalytic oxidation of cyanide used one semibatch reactor with ultraviolet irradiation 125W, in a pH range of 9.5 to 12. The catalyst with the highest percentage of degradation was HTiNbO5 93.7%, which is attributed to the microstructure of the double layer and Lewis acidity sites, followed by NbTi-1% 92.9% and the Nb2O5.3H2O 82.4%, being the majority product cyanate, proposing its mechanism of reaction. Characterization experiments indicated Nb-O-Ti bridges that have been associated to the control of redox properties of the niobium species and Ti-O-Nb = O, which could be generating a greater number of e–H +pairs increasing the photocatalytic activity. It is considered that the method of synthesis has a strong influence to change the morphology of the particles such as porosity, specific surface and factors such as the acidity of niobium–based catalysts, important to achieve efficiency in degradation. Niobium-Titanium photocatalysts proved to be an excellent new breakthrough in advanced oxidation Technologies (TOA), to eliminate cyanide in wastewater from mining activities.